2002
DOI: 10.1096/fj.02-0327fje
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C inhibits amyloid β‐peptide neurotoxicity by acting on members of the Wnt pathway

Abstract: Current evidence supports the notion that the amyloid beta-peptide (Abeta) plays a major role in the neurotoxicity observed in the brain in Alzheimer's disease. However, the signal transduction mechanisms involved still remain unknown. In the present work, we analyzed the effect of protein kinase C (PKC) on some members of the Wnt signaling pathway and its implications for Abeta neurotoxicity. Activation of PKC by phorbol 12-myristate 13-acetate protected rat hippocampal neurons from Abeta toxicity. This effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 43 publications
4
119
0
1
Order By: Relevance
“…Indeed, several PKC isoforms have been shown to phosphorylate and inactivate GSK-3 both ''in vivo '' and ''in vitro'' (Goode et al 1992;Fang et al 2002). In hippocampal neurons, direct PKC activators, such as phorbol esters, were reported to induce GSK-3 phosphorylation in Ser-9 and stabilisation of b-catenin, implying that several members of the Wnt signalling pathway are regulated by PKCs (Garrido et al 2002). In addition, different extracellular signals have been reported to use the PKC/GSK-3 signalling, such as LPA in Swiss 3T3 cells (Fang et al 2002), and muscarinic and PDGF receptors, which cooperate to regulate airway myocyte proliferation (Gosens et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several PKC isoforms have been shown to phosphorylate and inactivate GSK-3 both ''in vivo '' and ''in vitro'' (Goode et al 1992;Fang et al 2002). In hippocampal neurons, direct PKC activators, such as phorbol esters, were reported to induce GSK-3 phosphorylation in Ser-9 and stabilisation of b-catenin, implying that several members of the Wnt signalling pathway are regulated by PKCs (Garrido et al 2002). In addition, different extracellular signals have been reported to use the PKC/GSK-3 signalling, such as LPA in Swiss 3T3 cells (Fang et al 2002), and muscarinic and PDGF receptors, which cooperate to regulate airway myocyte proliferation (Gosens et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…5,12,31,[47][48][49][50] Considering that lithium is a pharmacological activator of the Wnt signaling pathway and rosiglitazone is a PPARg agonist that activates Wnt signaling by cross talk, 5,17 we wanted to confirm that under our experimental conditions, Wnt signaling was in fact activated. The expression of Wnt key proteins was analyzed by western blotting.…”
Section: Lithium and Rosiglitazone Treatment Reduces Inflammatory Reamentioning
confidence: 99%
“…Recent studies have shown that Wnt signaling is involved in neurodegenerative diseases, especially in acetylcholinesterase (AChE) and Ab-mediated neurotoxicity (Inestrosa et al, 2000;Garrido et al, 2002;De Ferrari et al, 2003). First, AChE is present in neuritic plaques in the AD brain (Geula and Mesulam, 1995;Guillozet et al, 1997), and can enhance Ab aggregation and plaque formation and may form AChE-Ab complexes (Alvarez et al, 1997).…”
Section: Introductionmentioning
confidence: 99%